Professor Saidi; Founder of the SSK Resident’s Forum - James Waweru (The Annals of African Surgery, 2018)
The resident’s forum is a chapter of the surgical society of Kenya formed by the associate members who are by large surgical residents and medical officers with interest in surgery. It is a platform for continuous surgical education and networking among the associate members. This forum has had a great impact on surgical trainees in the country for now six years, since inception by Professor Hassan. Professor Hassan held at heart, a great passion for teaching, his love commitment was like no other. Despite the ever growing number of students both in medical school and residency, professor juggled mentoring his students with commitment amidst work and family life. This, he fulfilled faithfully when there was so much more for him to do. He championed as a premier luminary of clinical practice to hundreds of medical students and residents. His teachings represented the truth in medical practice, correcting errors and advancing towards standard practice. He became a mentor to many students in University of Nairobi medical school and residents in Nairobi and Aga Khan University.